2020
DOI: 10.1073/pnas.2012149117
|View full text |Cite
|
Sign up to set email alerts
|

N - glycosylation shields Phytophthora sojae apoplastic effector PsXEG1 from a specific host aspartic protease

Abstract: Hosts and pathogens are engaged in a continuous evolutionary struggle for physiological dominance. A major site of this struggle is the apoplast. In Phytophthora sojae–soybean interactions, PsXEG1, a pathogen-secreted apoplastic endoglucanase, is a key focal point of this struggle, and the subject of two layers of host defense and pathogen counterdefense. Here, we show that N-glycosylation of PsXEG1 represents an additional layer of this coevolutionary struggle, protecting PsXEG1 against a host apoplastic aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…In plants, N-glycosylation is involved in many biological processes, including ER-quality control of steroid hormone receptor (Jin et al, 2007;Hong et al, 2008), gametophyte recognition (Lindner et al, 2015;Muller et al, 2016), subcellular transport (Rips et al, 2014;Shen et al, 2014), plant innate immunity (Li et al, 2009;Nekrasov et al, 2009;Haweker et al, 2010;Xia et al, 2020), and stomatal development (Jiao et al, 2020) by regulating the stability, function, or sub-localization of the substrate protein. Moreover, several studies also establish the association of N-glycosylation with salt tolerance in Arabidopsis (Koiwa et al, 2003;Kang et al, 2008;Nagashima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, N-glycosylation is involved in many biological processes, including ER-quality control of steroid hormone receptor (Jin et al, 2007;Hong et al, 2008), gametophyte recognition (Lindner et al, 2015;Muller et al, 2016), subcellular transport (Rips et al, 2014;Shen et al, 2014), plant innate immunity (Li et al, 2009;Nekrasov et al, 2009;Haweker et al, 2010;Xia et al, 2020), and stomatal development (Jiao et al, 2020) by regulating the stability, function, or sub-localization of the substrate protein. Moreover, several studies also establish the association of N-glycosylation with salt tolerance in Arabidopsis (Koiwa et al, 2003;Kang et al, 2008;Nagashima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When the pathogen invades the host, an extremely complex and precise arms race of 'attack and defence' occurs in the apoplastic space. Xia et al (2020) also proposed a 'multi-layered immune model' of the plants against pathogens in the extracellular region when studying the mechanism of action of PsXEG1 against Phytophthora sojae. Therefore, this study revealed the complexity of the interaction between pathogens and hosts as well as provided a theoretical basis to further study the role of TiAP1 in resistance mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, bioinformatics prediction of N‐ glycosylation suggests that many other effector proteins may also be N‐ glycosylated, and this may be important in their ability to suppress host immune responses. Recently, for example, it was found that in the oomycete pathogen Phytophthora sojae , N‐ glycosylation also shields an effector PsXEG1 against degradation by host aspartate proteases (Xia et al ., 2020).…”
Section: Regulatory Mechanisms Of Glycosylation In Biotrophic Establishment During Fungal Growth and Proliferationmentioning
confidence: 99%